Return to Physical Activity Following Flatfoot Reconstruction. (June 2022) - Fuller, Robert M.; Eble, Stephanie K.; Day, Jonathan; Cororaton, Agnes D.; Rajan, Lavan; Deland, Jonathan T.; Kumar, Prashanth; Ellis, Scott J.
Background: Progressive collapsing foot deformity (PCFD) is a debilitating condition encompassing several interrelated, progressive deformities requiring a combination of reconstructive procedures. Few studies investigate returns to activity following flatfoot reconstruction, and existing studies only examine 1 or 2 of the numerous procedures employed. This study aims to provide the first generalizable assessment of returns to sports and physical activity following reconstruction surgery in patients with flexible flatfoot deformity. Methods: Patients aged 18-60 years who underwent reconstructive surgery between February 16 and May 19 for symptomatic flexible-stage flatfoot deformity were identified by registry review. Eighty-two of 113 eligible patients (73%) were reached at a mean 2.9 years (range, 2.0-5.4) of follow-up with mean age at surgery of 48.9 years (range, 18-59). Returns to physical activity were evaluated with a sports-specific survey. Clinical outcomes were evaluated with Patient-Reported Outcomes Measurement Information System (PROMIS) scores. Results: Patients reported participation in 21 specific sports and activities. One-fourth (25.6%) of patients (21/82) reported increased difficulty with physical activities postoperatively, 15.9% reported equal difficulty, and 58.5% (48/82) reported decreased difficulty. Median return times were 9-12 months for participation and 12-18 months to reach maximum preoperative participation levels. Improvements in Physical Function ( P = .001), Pain Interference ( P < .001), Pain Intensity ( P <.001), and Global Physical Health ( P = .004) were associated with increased satisfaction with respect to sports and physical activities. Discussion: This study investigated participation in specific sports and physical activities following flatfoot reconstruction. Our findings suggest mixed outcomes, where many patients reported life-changing improvements but many also experienced prolonged pain and difficulty after surgery. Some patients reported increased difficulty or inability to return to their preoperative maximum level of participation, indicating that flatfoot reconstructions can lead to athletic limitations. Conclusion: Although flatfoot reconstruction can be a powerful tool to increase patients' capacity to engage in physical activity, in our cohort many patients had reduced physical activity outcomes. Level of Evidence: Level IV, retrospective case series.